PENGEMBANGAN EKOWISATA MANGROVE WONOREJO DI SURABAYA - Nani Azizah; Budi Rianto; Lunariana Lubis (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2020)
Food and Agriculture Security Service in Surabaya City is developing Mangrove Ecotourism in Wonorejo Surabaya which aims to find out the ecotourism development conducted by Surabaya City Food and Agriculture Security Service based on nature reserves. This study uses qualitative method with a case study approach and applies the theory from Gamal Suwantoro Tourism Development (2004) with the five indicators, namely: tourist objects and attractions, tourist infrastructure, tourist facilities, management/infrastructure, community and environment. The data collection is obtained through observation, interviews and documentation. The data analysis techniques use data collection, data condensation, data presentation and drawing conclusion. The results of this study indicates that the development of Mangrove Ecotourism in Wonorejo Surabaya has been applied well, but there are several inhibiting factors such as the lack of affordable public transportation, lack of coordination between agencies on tourist facilities on location signs, limited supply of souvenirs typical of mangroves, and the undeveloped environment.